Leptospirosis diagnosis among patients suspected of dengue fever in Brazil - Fornazari, Felipe [UNESP]; Richini-Pereira, Virginia Bodelao; Joaquim, Samea Fernandes [UNESP]; Nachtigall, Pedro Gabriel; Langoni, Helio [UNESP] (Cevap-sao Paulo State Univ-unesp, 2021)
Background: The early symptoms of leptospirosis and dengue fever are difficult to distinguish and can cause diagnostic confusion. Due to the large dengue epidemics that has occurred in Brazil in recent years, it is possible that cases of leptospirosis were unreported. Therefore, we performed a retrospective study to detect leptospirosis in patients who were tested for dengue, but whose laboratory diagnoses were negative. Methods: Sera samples from 2,017 patients from 48 cities located in the central region of Sao Paulo state, Brazil, were studied. All samples were subjected to the microscopic agglutination test (MAT), 305 of which were taken from patients five days or less since the onset of symptoms, and were additionally subjected to real-time polymerase chain reaction (PCR). Results: The overall prevalence of leptospirosis cases was 21 (1.04%), with 20 through MAT (18 for Icterohaemorrhagiae and two for the Cynopteri serogroup) and one through PCR (amplicon sequencing compatible with Leptospira interrogans). According to previously established criteria, eight cases of leptospirosis were classified as confirmed and 13 as probable. The Brazilian notification system for health surveillance had no records for 16 patients positive for leptospirosis and, thus, they were considered unreported cases. Statistical analyses revealed that the prevalence of leptospirosis was higher in men (1.56%) than in women (0.56%), and the mean age was higher in positive patients (43.7 years) than in negative ones (32.3 years). Conclusion: The results indicated that patients suspected of dengue fever had evidence of leptospirosis or Leptospira infection, and most of these cases were unreported in the Brazilian notification system. The high burden of dengue may contribute to the misdiagnosis of leptospirosis, and health professionals should increase their awareness of leptospirosis as an important differential diagnosis of patients with suspicion of dengue.
Keywords: Leptospira; Microscopic agglutination test; PCR; Unreported disease; Zoonosis